2007
DOI: 10.1103/physrevc.75.064901
|View full text |Cite
|
Sign up to set email alerts
|

Strange particle production inp+pcollisions ats=200GeV

Abstract: We present strange particle spectra and yields measured at midrapidity in √ s = 200 GeV proton-proton (p + p) collisions at the BNL Relativistic Heavy Ion Collider (RHIC). We find that the previously observed universal transverse mass (m T ≡ p T 2 + m 2 ) scaling of hadron production in p + p collisions seems to break down at higher m T and that there is a difference in the shape of the m T spectrum between baryons and mesons. We observe midrapidity antibaryon to baryon ratios near unity for and baryons and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
206
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 335 publications
(226 citation statements)
references
References 86 publications
(65 reference statements)
18
206
0
Order By: Relevance
“…The dashed curves in Fig. 24 show the prediction based on m T scaling [25,[59][60][61]. It is seen that the data are consistent with such scaling behavior.…”
Section: B η-To-pion Ratiosupporting
confidence: 52%
See 1 more Smart Citation
“…The dashed curves in Fig. 24 show the prediction based on m T scaling [25,[59][60][61]. It is seen that the data are consistent with such scaling behavior.…”
Section: B η-To-pion Ratiosupporting
confidence: 52%
“…The normalization is irrelevant because it cancels in the ratio γ decay /π 0 . To estimate the yields of the η and ω(782), we used the fact that these scale with the π 0 yields when expressed in terms of the transverse mass m T ≡ m 2 + p 2 T instead of p T [25,[59][60][61]. For the η spectra, we used the scaling ratios R η/π = 0.46 ± 0.05 for p + p and 0.44 ± 0.08 for d + Au data, as followed from our measurement of η production.…”
Section: E Background From Hadronic Decaysmentioning
confidence: 99%
“…The increase of the antimatter-to-matter ratio in heavy-ion collisions with the increase of center-of-mass energy has been observed by the NA49 [38,39] and STAR [40] Collaborations. Figure 1 shows changes of the p/p ratio with collision energy at mid-rapidity in central heavy-ion and in p + p collisions.…”
Section: Production Of Antibaryonsmentioning
confidence: 86%
“…This parameter was originally identified as the highest possible temperature for hadronic matter. Indeed, it was found that the m T spectra of different particle species (e.g., π − , K 0 , , ρ 0 , and ω) produced in hadronic collisions at center-of-mass energies of [8][9][10][11][12][13][14][15][16] GeV are reasonably well described by an exponential or Bose-Einstein distribution with the inverse slope parameter being independent of the particle mass [2,3]. Subsequently, the effect was called "m T -scaling" [4].…”
Section: Introductionmentioning
confidence: 99%